Infanticide in South Africa: A Case Study - Bergh, Lorinda Brink (Issues and Development in Health Research Vol. 2, 2021)
This article is about the therapeutic experience over a period of more than 10 years of a client convicted of murder (Infanticide). My client, for purposes of the article is referred to as “N”, then a young woman aged 19 when found guilty for the murder of her own infant[1], approximately 3-months old at the time of the murder. After a plea-bargain, she received a 15-year sentence of imprisonment of which 5 years was suspended for 5 years on condition she not be convicted of murder or any other offence of which violence is an element and for which she is sentenced to direct imprisonment committed in the period of suspension. Provided here is information pertaining to N’s background, how her case relates to Infanticide, her behaviour during incarceration, the outcome of her incarceration, and her subsequent release back into society.